Inovasi Pembelajaran Sejarah dalam Kurikulum Merdeka Tantangan dan Peluang Bagi Guru Sejarah: Innovation in History Learning in the Independent Curriculum: Challenges and Opportunities for History Teachers - Intan Febriyanti; M. Daffa Pratama; Shabrina Fillah; Syarifuddin Syarifuddin; Rani Oktapiani (Jurnal Ilmu Sosial dan Humaniora, 2026)
TThe Independent Curriculum provides teachers with greater opportunities to create unique, creative, and student-focused learning experiences. In the context of history learning, innovation is crucial for attracting students' interest in learning and enhancing critical thinking skills in the digital age. The purpose of this article is to examine innovations in history teaching under the Independent Curriculum and to identify the oppo rtunities and challenges educators face when implementing it. This study employed a literature review method by evaluating various scientific sources, including national journals related to history teaching, teaching strategies, and the implementation of the Independent Curriculum. Data analysis was conducted using descriptive qualitative methods, grouping the results based on central themes. The research findings indicate that innovations in history teaching can be implemented through various technology-based models and strategies, such as technology-based learning (TEL), which can strengthen student engagement and understanding of historical material. However, the implementation of these innovations still faces various challenges, such as a lack of digital skills among teachers, minimal training, and a lack of supporting facilities in educational institutions. Therefore, developing teacher competencies and providing support from educational institutions are crucial for realizing innovative, contextual history learning that is aligned with the needs of 21st-century education.